Neurons of the olfactory neurogenic region of the rat: a morphological study - Popovičová, Alexandra; Fabianová, Kamila; Martončíková, Marcela; Raček, Adam; Račeková, Enikő (Problems of Cryobiology and Cryomedicine, 2022)
Probl Cryobiol Cryomed 2022; 32(4):309